Effectiveness of Psychodynamic Therapy on Guilt and Loneliness in Women Affected by Marital Infidelity - Nazari, Ali; Ghorbani, Roya; Soltani, Mehdi; Gohari, Fatemeh; Siyadati, Seyede Mohsene; Pourmohammad Ghoochani, Kamran (Mental Health and Lifestyle Journal, 2024)
Marital infidelity, as a traumatic experience, can evoke profound feelings of guilt and loneliness in individuals, particularly in women who have been affected, and can have significant negative effects on their mental health. This study aimed to investigate the effectiveness of psychodynamic therapy on guilt and loneliness in women affected by marital infidelity. The research employed a quasi-experimental method with a pretest-posttest control group design. The statistical population consisted of women in Tehran who had been affected by marital infidelity. From this population, 30 participants were selected through convenience sampling and randomly assigned to experimental and control groups. The experimental group received psychodynamic therapy in 10 sessions of 90 minutes each, while the control group did not receive any intervention. Findings indicated that psychodynamic therapy significantly reduced feelings of guilt and loneliness in women affected by marital infidelity. The results suggest that psychodynamic therapy, by focusing on unconscious conflicts, past relationships, and emotional experiences during the therapeutic process, can improve the psychological state of these individuals. Therefore, it is recommended that this therapeutic approach be incorporated into psychotherapy programs for women dealing with marital infidelity.